The Thought of Wincenty Granat towards contemporary problems - Majchrzak, Jakub (Filozofia Chrześcijańska, 2021)
The aim of the article is to present relevance of the personalistic Granat’s thought in the context of contemporary social challenges. In the article, I analyze the topic of Christian humanism in Granat’s thought. I point out that he saw the sources of this concept in man’s aspirations to learn the full truth about himself. Granat saw the final answer to these desires in the relation of man and the sense of his existence to the person of Christ. I also consider Granat’s opinion about the role of the Catholic church today. I would like to draw your attention to the fact that Granat clearly emphasized the deep spiritual and apostolic dimension of the Church, pointing out that the Church is above all the Mystical Body of Christ. Therefore, the fundamental task of the Church is to unite God’s children around Christ. The Church also has a duty to proclaim to man that he cannot understand himself without Christ. The Church accomplishes these goals by administering the sacraments and moderating interreligious dialogue. I consider the issue of peace in his philosophical refl ection as well. According to Granat the source of peace is God. Man drawing his strength from his closeness with God can contribute to peace through mutual respectful relationships. At the state level the key role is played by the concern of each country for the common good and international cooperation in this field. In conclusion, I formulate summarizing remarks.